Tinjauan Hukum Tentang Eksploitasi Anak di Kota Semarang - Muchtolip Muchtolip (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The phenomenon of street children which is rife in Semarang creates complex social problems. A lot of street children being exploited by several parties or even their own parents is caused by several factors and one of the biggest and most basic factors is the economic factor. Researchers made this research to find out what factors influence children to be exploited and become buskers or even beggars on the streets. And the second discussion that based on this research is the impact of the exploitation of the child itself. Some of the reasons that might trigger the child to become a victim of exploitation are from an economic point of view, which is very lacking from the family. Another possibility may also be due to environmental influences and limited thinking. Which causes the psychological aspect of the child to be disturbed, for example the child will have a begging mentality or even towards crime. Another possible impact is the health of the child who is exposed to too much sun, vehicle emission and so on.